Extraction of microcrystalline cellulose (mcc) from cocoa pod husk via alkaline pretreatment combined with ultrasonication - Jimat, Dzun Noraini; Wan Salim, Wan Wardatul Amani; Avicenna, Avicenna; Ahmad Zailani, Ima Shahanaz (2015)
The aim of this study was to extract microcrystalline cellulose (MCC) from cocoa pod husk (Theobroma cacao L.) via alkaline treatment and ultrasonication. The sieved cocoa pod husk (CPH) was treated with 2% w/v sodium hydroxide (NaOH) for 5h at 80oC in a water bath. Then, it was bleached by aqueous dilution of hydrogen peroxide at 75oC followed by treating with 12% w/v NaOH at 80oC for 1h. Ultrasonication was conducted after completion of alkaline treatment to isolate fibrils aggregates to form MCC. Response surface methodology (RSM) using Design expert @version 8.0) was used to determine the optimum condition of ultrasonication by varying its ultrasonication time and cycle with particle size of MCC as response. Analysis of variance (ANOVA) of this study showed that both parameters are significantly affects the particle size of MCC. The optimized condition postulated from the RSM are 60 s of sonication time with 2 cycles. It was found that the smallest particle size of samples was 286 nm. Results from scanning electron microscope images showed that the surface structure of the solid CPH differed over the stage of the whole processes.